Comportamento empoderador do líder na perspectiva dos liderados - Graça, Elinalva Priscila Soares da [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Introduction: In Brazil, the nursing work process involves processes from the perspective of caring/assistance, administering/managing, teaching/educating and researching. These processes are developed having as a component the technical division of work that involves the different categories: nurses, nursing technicians and nursing assistants. The good relationship between nurses and their staff creates an environment conducive to a high level of care and patient care. The empowerment of nurses tends to create a better work environment and greater communicability among the nursing staff. Aim: To understand the behavior of nurses in the empowerment of their team from the perspective of nursing technicians and assistants Method: Exploratory, descriptive, cross-sectional and correlational study. Participants were 260 mid-level nursing professionals (technicians and nursing assistants) from the Hospital das Clínicas of the Faculty of Medicine of Botucatu. Data collection used a questionnaire with socio-demographic and labor data: professional category (technician or nursing assistant), gender, age, workplace, weekly workload, working time at the institution, other employment relationships, satisfaction with the work and the “Leader Empowering Behavior” (CEL) scale with 27 items divided into five domains. The response scale is of the Likert type, which varies between one and seven points, indicating that the higher the score, the greater the presence of attributes favorable to the practice of empowerment. The project was approved by the Research Ethics Committee of Universidade Estadual Paulista-UNESP Botucatu, CAAE: 12221719.2.0000.5411, Opinion number: 4,730.604. Findings: The profile of the participants is female, with a mean age of 41.9 years, daytime workers, workload of 36.7 hours and satisfied with their work. The application of the instrument "Leader Empowering Behavior" (CEL) showed that the domain with the highest average of empowering behavior was "Significant work" and the one with the lowest average was the domain "Autonomy in relation to bureaucracy", the domains "Taking action participatory decision, "Employee confidence" and "Facilitating the achievement of goals" had similar means. Conclusion: The nurse's behavior to empower his team, from the perspective of nursing technicians and assistants in the studied hospital, was considered good in most domains. Only in the domain autonomy in relation to bureaucracy was the leader's behavior to empower his team reasonable.

Introdução: No Brasil o processo de trabalho em Enfermagem envolve processos na perspectiva do cuidar/assistir, administrar/gerenciar, ensinar/educar e pesquisar. Esses processos são desenvolvidos tendo como componente a divisão técnica do trabalho que envolve as diferentes categorias: enfermeiros, técnicos de enfermagem e auxiliares de enfermagem. O bom relacionamento de enfermeiros com a sua equipe cria um ambiente propício de alto nível para um trabalho de cuidado e atenção ao paciente. O empoderamento de enfermeiros tende a criar um melhor ambiente de trabalho, e uma maior comunicabilidade entre a equipe de enfermagem. Objetivo: Conhecer o comportamento do enfermeiro no empoderamento de sua equipe na perspectiva dos técnicos e auxiliares de enfermagem. Método: Estudo exploratório, descritivo, transversal e correlacional. Os participantes foram 260 profissionais de enfermagem de nível médio (técnicos e auxiliares de enfermagem) do Hospital das Clínicas da Faculdade de Medicina de Botucatu. A coleta de dados utilizou um questionário com dados sócio-demográficos e laborais: categoria profissional (técnico ou auxiliar de enfermagem), sexo, idade, local de trabalho, carga horária semanal, tempo de trabalho na instituição, outros vínculos de trabalho, satisfação com o trabalho e a escala “Comportamento Empoderador do Líder” (CEL) com 27 itens divididos em cinco domínios. A escala de respostas é do tipo Likert, que varia entre um e sete pontos, indicando que, quanto maior a pontuação, maior a presença de atributos favoráveis à prática de empoderamento. O projeto foi aprovado pelo Comitê de Ética em Pesquisa da Universidade Estadual Paulista-UNESP Botucatu, CAAE: 12221719.2.0000.5411, Parecer número: 4.730.604. Resultados: O perfil dos participantes é do sexo feminino, com média de idade de 41,9 anos, trabalhadores do período diurno, carga horária de 36,7 horas e satisfeitos com o trabalho. A aplicação do instrumento “Comportamento Empoderador do Líder” (CEL) evidenciou que o domínio com maior média de comportamento empoderador foi o “Trabalho significativo” e o com menor média foi o domínio “Autonomia em relação à burocracia”, os domínios “Tomada de decisão participativa”, “Confiança dos funcionários” e “Facilitando o alcance das metas” tiveram médias similares Conclusão: O comportamento do Enfermeiro para empoderar sua equipe, na perspectiva dos técnicos e auxiliares de Enfermagem no hospital estudado, foi considerado bom na maioria dos domínios. Apenas no domínio autonomia em relação à burocracia o comportamento do líder para empoderar sua equipe foi razoável.
Empowering behavior of the leader from the perspective of the followers
Keywords: Liderança; Equipe de enfermagem; Gerenciamento da prática profissional; Prática baseada em evidências; Enfermagem